1985
DOI: 10.1073/pnas.82.20.7140
|View full text |Cite
|
Sign up to set email alerts
|

Peptidergic modulation of patterned motor activity in identified neurons of Helisoma

Abstract: The neuroaftive peptides SCPB (small cardioactive peptide B) and FMRFamide (Phe-Met-Arg-Phe-NH2), both originally isolated from molluscs, have potent modulatory effects upon the production of patterned motor activity in identified neurons (e.g., B5 and B19) in the buccal ganglia of the snail Helisoma. Such patterned motor activity has previously been shown to underlie feeding behavior. (7,8).Several aspects of the neural basis of feeding in the snail Helisoma trivolvis have been described. Cyclical activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 21 publications
(23 reference statements)
3
46
0
Order By: Relevance
“…The use of a SEEPLY-antiserum revealed a unique immunoreactive pair of cells within the buccal ganglia with axonal projections into the laterobuccal nerve, innervating the buccal mass. Thus it appears that Lymnaea differs from Helisoma and Aplysia where several FMRFamide-immunoreactive pairs of cells were detected in the buccal ganglia (Murphy et al, 1985;Church and Lloyd, 1991).…”
Section: Peptide Distribution In the Feeding Network And Associated Tmentioning
confidence: 95%
“…The use of a SEEPLY-antiserum revealed a unique immunoreactive pair of cells within the buccal ganglia with axonal projections into the laterobuccal nerve, innervating the buccal mass. Thus it appears that Lymnaea differs from Helisoma and Aplysia where several FMRFamide-immunoreactive pairs of cells were detected in the buccal ganglia (Murphy et al, 1985;Church and Lloyd, 1991).…”
Section: Peptide Distribution In the Feeding Network And Associated Tmentioning
confidence: 95%
“…Buccal peptidegic neurons innervating the foregut similar to that described here for Bc-FG cells were identified in several gastropod species: Aplysia , B2 in Lymnaea (Perry et al, 1998), B5 in Helisoma (Murphy and Kater, 1980;Murphy et al, 1985) and B11/B12 in Tritonia (Lloyd and Willows, 1988). All these cells have a similar morphology: a large cell body and main neurite leaving the CNS through the gastro-esophageal nerve and innervating the foregut.…”
Section: Buccal Foregut Neurons In Gastropodsmentioning
confidence: 58%
“…Previous studies have shown a wide variety of central actions of SCPs in Aplysia (Abrams et al 1984;Ocorr and Byrne 1986;Sossin et al 1987;Alevizos et al 1989;Kirk 1989;Plummer and Kirk 1990;Taussig et al 1989), as well as in Limax (Prior and Watson 1988;Hess and Prior 1989), Tritonia (Lloyd and Willows 1980;Willows et al 1988), and Helisoma (Murphy et al 1985). For example, in the abdominal ganglia of Aplysia, the R20 neurons modulate respiratory pumping by exciting the cells of the R25/L25 network.…”
Section: Discussionmentioning
confidence: 96%